Performance of leaf beetle larvae on sympatric host and non-host plants - Ballabeni, Pierluigi; Rahier, Martine (My University, 2000)
Studies asking the ability of insects to utilize novel host plants often use novel hosts that are allopatric with the insect population under investigation. However, since the outcomes of species interactions are often site-specific, such studies cannot tell us whether a plant would actually be used by a given insect population if the plant grew sympatrically with it. We therefore performed a quantitative genetics experiment to analyse the performance of larvae of the leaf beetle Oreina elongata Suffrian (Coleoptera: Chrysomelidae, Chrysomelinae) on two host and three non-host plants, collected from a site where insects and plants co-occur in the Western Alps. When raised on the non-host Petasites albus (L.), larvae were able to survive equally well as on the two hosts, Adenostyles alliariae (Gouan) and Cirsium spinosissimum (L.), whereas they did not survive on the two other non-hosts, Peucedanum ostruthium (L.) and Rumex alpinus L. On P. albus, growth rate was slightly lower and development time slightly longer than on the two hosts. We found a genotype by environment interaction only for growth rate but not for development time and survival. However, the shape of the reaction norms of growth rates suggests that it is unlikely that selection could favour the inclusion of P. albus into the host range of the study population.Studies asking the ability of insects to utilize novel host plants often use novel hosts that are allopatric with the insect population under investigation. However, since the outcomes of species interactions are often site-specific, such studies cannot tell us whether a plant would actually be used by a given insect population if the plant grew sympatrically with it. We therefore performed a quantitative genetics experiment to analyse the performance of larvae of the leaf beetle Oreina elongata Suffrian (Coleoptera: Chrysomelidae, Chrysomelinae) on two host and three non-host plants, collected from a site where insects and plants co-occur in the Western Alps. When raised on the non-host Petasites albus (L.), larvae were able to survive equally well as on the two hosts, Adenostyles alliariae (Gouan) and Cirsium spinosissimum (L.), whereas they did not survive on the two other non-hosts, Peucedanum ostruthium (L.) and Rumex alpinus L. On P. albus, growth rate was slightly lower and development time slightly longer than on the two hosts. We found a genotype by environment interaction only for growth rate but not for development time and survival. However, the shape of the reaction norms of growth rates suggests that it is unlikely that selection could favour the inclusion of P. albus into the host range of the study population.Studies asking the ability of insects to utilize novel host plants often use novel hosts that are allopatric with the insect population under investigation. However, since the outcomes of species interactions are often site-specific, such studies cannot tell us whether a plant would actually be used by a given insect population if the plant grew sympatrically with it. We therefore performed a quantitative genetics experiment to analyse the performance of larvae of the leaf beetle Oreina elongata Suffrian (Coleoptera: Chrysomelidae, Chrysomelinae) on two host and three non-host plants, collected from a site where insects and plants co-occur in the Western Alps. When raised on the non-host Petasites albus (L.), larvae were able to survive equally well as on the two hosts, Adenostyles alliariae (Gouan) and Cirsium spinosissimum (L.), whereas they did not survive on the two other non-hosts, Peucedanum ostruthium (L.) and Rumex alpinus L. On P. albus, growth rate was slightly lower and development time slightly longer than on the two hosts. We found a genotype by environment interaction only for growth rate but not for development time and survival. However, the shape of the reaction norms of growth rates suggests that it is unlikely that selection could favour the inclusion of P. albus into the host range of the study population.
Keywords: larval performance; trade-off; reaction norms; host range evolution; leaf beetle; Oreina; Chrysomelidae